Transitivity Analysis of Emily Dickinson’s Poem Entitled “I Cannot Live with You” - Amiqi, Maftuch Fahman Al; Sunardi, Sunardi (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2024)
This research aims to identify the types of processes, related participants, circumstances, and the field of discourse in Emily Dickinson’s poem entitled “I Cannot Live with You”. The method used is a descriptive qualitative method with the Halliday theory approach on Transitivity Process. The analysis discovered 7 types of transitivity processes and 57 participants, with the dominant types of processes are Material and Relational:Attributive with 12 processes (33.33%). Correspondingly, the most frequent participants were related to the Relational:Attributive Process, particularly the Carrier and Attribute which appeared 12 times (21.05%). Additionally, 4 types of circumstances were identified, totaling 16 instances, with the Circumstance of Accompaniment being the most common with 6 occurrences (40%). The field of discourse in Emily Dickinson’s poem entitled “I Cannot Live with You” is to tell that love cannot last forever.